Factors associated with maternal obesity and its outcomes among pregnant women in Klang valley a review from national obstetric registry 2015 - Shahrir, Nurul Farehah (2018)
Background The increasing prevalence of maternal obesity worldwide is a public health concern. It is well recognized that maternal obesity was associated with adverse fetal and maternal outcomes. Objective This study aims to determine the proportion, associated factors and outcomes of maternal obesity among pregnant women in Klang Valley in 2015. Methodology A cross sectional study was conducted between January to March 2018 using secondary data from National Obstetric Registry. All pregnant women with first trimester booking at 12 week and below, registered in National Obstetric Registry from Klang Valley in 2015 who fulfilled the inclusion and exclusion criteria were included in the study. No sampling method was applied. All information was collected using proforma. A total of 2113 were included in this study for determination of proportion according to WHO (1995) and MOH (2003) cut off points, however underweight was excluded for subsequent analyses. In maternal and fetal outcomes, respondents were classified into two groups which were normal and obese which comprised of overweight and obese and group. Result According to WHO (1995) BMI cut offs points, 149 (7.1%) were underweight, 881 (41.7%) normal weight, 604 (28.6%) overweight, 336 (15.9%) obese class I, 98 (4.6%) obese class II, and 45 (2.1%) obese class III. However, when the Asian BMI cut off point was used, there was marked increased in the proportion of maternal overweight by 2.7% and obesity class 1 by 12.8%. Ethnicity which were Indian ( AOR 2.06, 95% CI: 1.11, 3.83, p = 0.021 ) , and Malay ( AOR 1.75, 95% CI : 1.02, 3.00 , p=0.040) and parity which were multiparity ( AOR : 1.46, 95% CI: 1.23,1.73, p<0.001) and grandmultipara (AOR 2.41 , 95% CI :1.78, 3.26 , p < 0.001) were significantly associated with maternal obesity . There were significant association between maternal obesity with hypertensive disorder in pregnancy (p=0.025), caesarean section delivery (p=0.002) and macrosomic infant (p <0.001). Conclusion Identification of risk factors among maternal obesity allow intervention programme to focus on high risk group women to lower the risk of adverse maternal and fetal outcomes.